(untitled) (International Journal of Engineering and Computer Science, 2013)
A Photovoltaic (PV) system’s power output is not constant and fluctuates depending on weather conditions. Fluctuating power causes frequency deviations in the power utilities when PV power penetration is large.Using a battery is the common practice to smooth PV output power fluctuations. In this paper, we propose and simple fuzzy based control method for PV-diesel hybrid system to reduce frequency deviations without smoothing PV output power fluctuations. By means of the proposed method, output power control of PV system considering the conditions of power utilities and maximizing energy capture are achieved.This paper presents a low cost high efficiency transformer isolated micro-inverter for single-phase grid connected photovoltaic (PV) system. The proposed micro inverter is composed of two stages, an isolated dcdc converter stage and an inverter stage with a dc link. A high frequency transformer isolated high voltage gain boost half-bridge dc-dc converter is used at the first stage to achieve maximum power point tracking (MPPT) and to step up the PV voltage to the high voltage dc-link. A pulse width modulated (PWM) full-bridge inverter with LCL filter is used at the second stage to output the synchronized sinusoid current with unity power factor to the grid. By utilizing the transformer leakage inductance, two primary side switches can achieve zero voltage switching (ZVS). A 210 W prototype of the proposed micro-inverter has been built and tested. The efficiency of the proposed boost half-bridge dc-dc converter has been measured according to the PV curve, which is up to 98.2%. Experimental results are provided to demonstrate the validity and features of the proposed circuit.